(untitled) (Academia Journal of Medicine, 2025)
Current research suggests an emerging value of 3D printed guides use in the endodontic field. Computer-aided design and manufacturing technologies can be used to create 3D printed guides with endodontic clinical applications. Computer aided design (CAD) and computer-aided manufacturing (CAM) technologies can leverage cone beam computed tomography data for production of objects used in surgical and nonsurgical endodontics and in educational settings. The aim of this article was to review all current applications of 3D printing in endodontics and to speculate upon future directions for research and clinical use within the specialty. Documented solutions to endodontic challenges include: guided access with pulp canal obliteration, applications in auto transplantation, pre-surgical planning and educational modelling and accurate location of osteotomy perforation sites. Future research directions should include clinical outcomes assessments of treatments employing 3D printed objects.